2018
DOI: 10.1002/solr.201800243
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Mo Back Contact with MoO3−x Layer and its Effect to Enhance the Performance of Cu2ZnSnS4 Solar Cells

Abstract: Kesterite Cu2ZnSnS4 (CZTS) has been investigated intensively as a promising absorber material for thin film solar cells. However, the reported best power conversion efficiency (PCE) is still low due to the intrinsic limitations of CZTS defects and the unfavorable front and back contact interfaces. In this study, an intermediate MoO3−x layer is introduced as a primary back contact prior to the Cd‐doped Cu2ZnSnS4 (CZCTS) absorber layer growth. It has been demonstrated that the insertion of the MoO3−x layer can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The RTP‐treated samples were further annealed to 200 °C on a hotplate in air for 10 min before CdS buffer growth. Using chemical bath deposition (CBD), [ 24 ] an ≈60 nm thick CdS buffer layer was grown onto the CZTS surface, which was subsequently annealed at 270 °C for 10 min in an oven immediately after CdS growth. A 50 nm i‐ZnO window layer and 500 nm AZO front contact layer were finally deposited using RF magnetron sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…The RTP‐treated samples were further annealed to 200 °C on a hotplate in air for 10 min before CdS buffer growth. Using chemical bath deposition (CBD), [ 24 ] an ≈60 nm thick CdS buffer layer was grown onto the CZTS surface, which was subsequently annealed at 270 °C for 10 min in an oven immediately after CdS growth. A 50 nm i‐ZnO window layer and 500 nm AZO front contact layer were finally deposited using RF magnetron sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-section SEM images of selenized CIS film coated (a) on Molybdenum, (b) directly on glass, (c) on 10 nm MoO3 coated Molybdenum, and (d) on 5 nm MoO3 coated Molybdenum A similar phenomenon was observed in literature for Cu 2 ZnSnSe 4 (CZTSe) thin films fabricated via selenization of sulfide Cu 2 ZnSnS 4 (CZTS) films.A film deposited on Mo substrate grew as 2 layers of grains while the one deposited on glass grew into single grain morphology 20. Other similar studies suggest the use of a thin layer of SiO 2 , TiN, MoO 3 on the Mo surface to change the interface between precursor material and back contact [20][21][22][23]. While no such surface modifications for changing grain morphology were studied in the case of CISe/CIGSe thin films, one study showed that a thin layer of MoO 3 layer between CIGSe absorber and Mo back contact improves the band alignment of CIGSe devices 24.…”
mentioning
confidence: 89%
“…20 Other similar studies suggest the use of a thin layer of SiO 2 , TiN, MoO 3 on the Mo surface to change the interface between precursor material and back contact. [20][21][22][23] While no such surface modifications for changing grain morphology were studied in the case of CISe/CIGSe thin films, one study showed that a thin layer of MoO 3 layer between CIGSe absorber and Mo back contact improves the band alignment of CIGSe devices. 24 To study the effect of surface modification on grain morphology and device performance, 10 nm of MoO 3 was deposited on the Mo surface via thermal evaporation at the rate of 0.02-0.03 nm/s.…”
Section: Figure 1 Ftir Data Collected On Cis Films Coated With Two Di...mentioning
confidence: 99%
“…[ 28 ] On the other hand, the insertion of a barrier layer on top of Mo is widely adopted to modify the back contact. Barrier layers, such as MoO 2 , [ 29 ] MoO 3 , [ 30,31 ] TiB, [ 32 ] Na 2 S, [ 33 ] carbon, [ 34 ] Al‐doped ZnO (AZO), [ 35 ] TiN, [ 36,37 ] and a temporary alloy layer, [ 38 ] have been demonstrated to be helpful to suppress the Mo(S x ,Se 1− x ) 2 thickness and enhance the device performance. However, these methods unexceptionally need an extra process to introduce the blocking layers and increase the risk of introducing impurity elements into the absorber.…”
Section: Introductionmentioning
confidence: 99%